2011
DOI: 10.1177/0734904111423499
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of simplified calculation methods for determining heat transfer between a smoke flow and a sprinkler spray

Abstract: Empirical equations determining heat transfer between a smoke layer and a sprinkler spray have been assessed by using data from several experiments available in the literature. The comparison of the heat loss and temperature of the smoke layer under sprinkler spray shows that the equations developed by Williams for 15 mm pendent conventional sprinklers agree reasonably well with the experimental results. Equations from Spearpoint et al. (Spearpoint MJ, Williams C and Morgan HP. Engineering relationships for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Mathematical models [18,19] were developed to estimate the influence of droplet drag force in affecting the buoyancy driven smoke layer and were validated against experimental data. Similar studies [20,21] were reported to evaluate heat loss from smoke to water particles by correlating empirical relations with experimental predictions.…”
Section: Introductionmentioning
confidence: 81%
“…Mathematical models [18,19] were developed to estimate the influence of droplet drag force in affecting the buoyancy driven smoke layer and were validated against experimental data. Similar studies [20,21] were reported to evaluate heat loss from smoke to water particles by correlating empirical relations with experimental predictions.…”
Section: Introductionmentioning
confidence: 81%
“…Several analytical approaches have been proposed to assess the downward displacement of the smoke layer as well as the heat transferred from the smoke to the droplet flow. () Some studies also point out this influence on the doorway flow or the vent flow. ()…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical approaches have been proposed to assess the downward displacement of the smoke layer as well as the heat transferred from the smoke to the droplet flow. [4][5][6][7][8][9] Some studies also point out this influence on the doorway flow or the vent flow. [10][11][12] Very few studies on forced-ventilated compartment configurations have been performed in the scientific community.…”
Section: Introductionmentioning
confidence: 99%